Faktor Kesulitan Belajar Siswa Kelas II dalam Memahami Konsep Penjumlahan dan Pengurangan di SDN Bandung I Jombang - Afifatun Nahdiyah; Evi Rizqi Salamah (Prodi Pendidikan Guru Sekolah Dasar, 2026)
Assisting second-grade elementary school students in mathematics learning, particularly in understanding the concepts of addition and subtraction, remains an important issue to study. This study aims to analyze the factors influencing students' learning difficulties in understanding these concepts, including internal factors (learning interest, conceptual understanding, learning readiness) and external factors (teacher teaching methods, media use, and the learning environment). The study used a qualitative descriptive approach using observation, interviews, and documentation techniques. The results indicate that students' learning difficulties arise from a lack of understanding of basic arithmetic concepts, low learning motivation, a lack of varied learning methods, and a lack of concrete media used by teachers. This study concludes that improving understanding of addition and subtraction concepts can be achieved through the use of concrete learning models, structured exercises, and active student involvement in the learning process.